A national survey of private-sector outpatient care of sick infants and young children in Nepal - Bharat Ban; Stephen Hodgins; Pranita Thapa; Surakschha Thapa; Deepak Joshi; Adhish Dhungana; Anjana KC; Tanya Guenther; Shilu Adhikari; Elaine Scudder; Pavani K. Ram (BMC, 2020)
Abstract Background Previous research has documented that across South Asia, as well as in some countries in Sub-Saharan Africa, the private sector is the primary source of outpatient care for sick infants and children and, in many settings, informal providers play a bigger role than credentialed health professionals (particularly for the poorer segments of the population). This is the case in Nepal. This study sought to characterize medicine shop-based service providers in rural areas and small urban centers in Nepal, their role in the care and treatment of sick infants and children (with a particular focus on infants aged < 2 months), and the quality of the care provided. A secondary objective was to characterize availability and quality of such care provided by physicians in these settings. Methods A nationally representative sample of medicine shops was drawn, in rural settings and small urban centers in Nepal, from 25 of the 75 districts in Nepal, using multi-stage cluster methodology, with a final sample of 501 shops and 82 physician-run clinics. Face-to-face interviews were conducted. Results Most medicine shops outside urban areas were not registered with the Department of Drug Administration (DDA). Most functioned as de facto clinics, with credentialed paramedical workers (having 2-3 years of training) diagnosing patients and making treatment decisions. Such a role falls outside their formally sanctioned scope of practice. Quality of care problems were identified among medicine shop-based providers and physicians, including over-use of antibiotics for treating diarrhea, inaccurate weighing technique to determine antibiotic dose, and inappropriate use of injectable steroids for treating potentially severe infections in young infants. Conclusions Medicine shop-based practitioners in Nepal represent a particular type of informal provider; although most have recognized paramedical credentials, they offer services falling outside their formal scope of practice. Nevertheless, given the large proportion of the population served by these practitioners, engagement to strengthen quality of care by these providers and referral to the formal health sector is warranted.